Low-Density Lipoprotein Cholesterol Levels in Coronary Artery Disease Patients: Opportunities for Improvement. (27th April 2022) - Martin, Gary J.; Teklu, Meron; Mandieka, Edwin; Feinglass, Joe
Abstract : Background . We sought to characterize the level of LDL-C control and identify opportunities for improvement and characteristics of patients who were undertreated. Methods . Study patients were from a large multihospital system, age <90, with documentation of at least two encounters with a CAD diagnosis or procedure before a first measured LDL-C level and a last recorded LDL-C measurement over a minimum six-month (median = 22 months, IQR = 15–26 months) follow-up from January 2017 to September 2019. Linear regression analysis for last recorded LDL-C level was used to analyze the effects of statin intensity and patient characteristics. Results . Among 15, 111 eligible patients, mean age was 68.4 (SD = 10.8), 68.7% were male, and 79.4% were non-Hispanic White. At follow-up, 87.8% of patients were prescribed a statin, 9.7% were on ezetimibe, and 0.5% were on a PCSK9 inhibitor. Mean LDL-C at follow-up was 75.6 mg/dL and 45.5% of patients were on high-intensity treatment. Higher LDL-C values were associated with female sex, younger patients, non-Hispanic Black patients, high poverty or out of state zip code, Medicaid, or angina as the qualifying diagnosis. For 332 clinicians with >10 patients in the cohort, mean last recorded LDL-C values ranged from 47 to 102 mg/dL. Conclusions . There were important variations in LDL-C control between patients in our health system with the same indication for treatment. Variation in treatment among physicians is an area ripe for quality improvement interventions. This study may be easily reproduced by other medical centers and used for highlighting both patient and physician opportunities for improvement.